THE EFFECT OF AFFECTIVE COMMITMENT ON TEACHER PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE AT YAPINI AL-IKHWAN ISLAMIC EDUCATION FOUNDATION NURUL ILMI, LHOKSEUMAWE CITY - Fitrah Khairunnajwa; Marbawi; Sullaida; Nur Faliza (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to analyze the effect of affective commitment on teacher performance with job satisfaction as an intervening variable in Yapini Al-Ikhwan Islamic Education Foundation Nurul Ilmi Lhokseumawe City. This study uses a quantitative approach with a sample of 42 respondents. Data analysis was carried out with the help of SPSS software version 26 using the path analysis method. The results of the simultaneous test (F test) showed that the variables of affective commitment and job satisfaction together had a significant effect on teacher performance, with an Fcal value of 25.531 and a significant value of 0.000 < 0.05. The results of the partial test (t-test) in the first model showed that affective commitment had a significant effect on job satisfaction, with a t-value of 4.550 > a ttable of 2.023. The coefficient of determination (R²) in the first model was 34.1%. In the second model, affective commitment had a significant effect on teacher performance with a score of 2.340 > table of 2.023, and job satisfaction also had a significant effect on teacher performance with a score of 4.114 > table of 2.023. The coefficient of determination (Adjusted R²) in the second model was 54.5%. These findings affirm the importance of strengthening affective commitment and increasing job satisfaction as factors that can encourage improved teacher performance.